2011
DOI: 10.1111/j.1365-2710.2011.01300.x
|View full text |Cite
|
Sign up to set email alerts
|

Discontinuation of angiotensin-converting enzyme inhibitors: a cohort study

Abstract: Physicians should pay attention to adherence problems particularly when prescribing ACEI to male patients, those who are older than 70 years, have no comorbidity, live in less urbanized or more rural areas, qualify for fee-waiver, are new attendees of consultations or obtain their ACEI prescriptions in FMSC. Future research should evaluate the reasons for ACEI discontinuation among these higher-risk groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…After multivariate correction, age was still significant a factor associated with higher mortality. Apart from the logic increase in mortality with increasing age, another contributing factor might be the overall lower compliance in older patients [17,18]. Whether closer follow-up or better patient education might improve compliance and therefore decrease mortality requires further research.…”
Section: Discussionmentioning
confidence: 95%
“…After multivariate correction, age was still significant a factor associated with higher mortality. Apart from the logic increase in mortality with increasing age, another contributing factor might be the overall lower compliance in older patients [17,18]. Whether closer follow-up or better patient education might improve compliance and therefore decrease mortality requires further research.…”
Section: Discussionmentioning
confidence: 95%
“…Data regarding social background, degree of education, physical exercise, diet, alcohol consumption and smoking history, which may all contribute to explaining the gender gap in control of CVD risk factors, were not available. Lack of information on medication dispensing, dosage and adherence further limits speculation on the role of treatment differences, although women are generally more compliant than men with regard to taking medication [15,43,44]. The fact that the male/female ratio in the present cohort (57:43) is higher than that of diabetic subjects from the general population in Italy [45,46], but similar to that reported from a coeval survey in the secondary care setting [47], suggests a selection bias for referral to specialists.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in some studies in the literature, adherence to pharmacological treatment is not associated with socio-demographic characteristics. 7,21,22,26 On the other hand, some studies have indicated that sociodemographic characteristics such as age, gender, level of education, perceived income status are related to adherence to the pharmacological treatment. 3,21,26 For example, while adherence to treatment increases in some studies as the age increases it decreases in other studies.…”
Section: Discussionmentioning
confidence: 99%
“…7,21,22,26 On the other hand, some studies have indicated that sociodemographic characteristics such as age, gender, level of education, perceived income status are related to adherence to the pharmacological treatment. 3,21,26 For example, while adherence to treatment increases in some studies as the age increases it decreases in other studies. 8,23,27 In these studies, an increase or decrease in the rate of adherence to the treatment with age may be due to the presence of comorbid chronic diseases, perceived health status, or differences in giving or receiving health care.…”
Section: Discussionmentioning
confidence: 99%